Answer:
Explanation:
1. (2m - 8n + 6) + (4n - 3) = 2m - 4n +3
2. (4y2 - 3xy + x2) + (y2 + 3xy + 3x2) = 4 - 6xy + 4x2
3. (8x + 7) + (2x - 6) = 10x + 1
4. (n + 5) + (2n + 7) = 3n + 12 which can also be written as common factor; 3(n +4).
5. (2a + 8) + (a + 2) = 3a + 10
6. (4m + 3n - p) + (2p - 3n + 2m) = 6m + p
7. (5x2 - 3x + 6) + (x2 + 5x - 15) = 6x^2 + 2x - 9
8. (3d - 4e + 6) + (2d +5e + 1) = d - e + 6
9. (5x - 3y) + (10y - 4z) + (2x - 3z) = 7x + 7y - 7z
10. (2a + 3) + (a - 9) = 3a - 6, common factor 3 (a-2)